Parental investment in eggs and its effect on nestling growth and survival in Magellanic Penguins - Barrionuevo, Melina (2014)
Life-history variables evolve in response to cost-benefit trade-offs. For birds, larger eggs are thought to be beneficial for development of offspring but are energetically costly to produce. Further, egg-size dimorphism within or between clutches can vary with proximate and ultimate causes. We undertook a correlational study to evaluate parental investment in eggs by Magellanic Penguins (Spheniscus magellanicus) and how it affects the growth and survival of nestlings in Puerto Deseado, Argentina, over 3 years. We evaluated the variables that affected egg-volume and yolk-area (using a nondestructive technique), and determined the effects of egg-volume and yolk-area on growth and survival of young. Females in good body-condition laid larger second eggs and, in good years (i.e. years of high reproductive success in the colonies of the study area), yolk-area of second eggs was larger than that of first eggs. We found a positive association between egg-volume and nestling body-size and yolk-area was positively related to nestling survival. Our results suggest that the size of eggs within clutches varied with year and female body-condition. Moreover we demonstrate for the first time that yolk-area is a strong predictor of nestling survival in Magellanic Penguins.